2013
DOI: 10.1039/c3ay41393d
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium distribution sampling device for preparation of calibration mixtures for gas chromatography-mass spectrometry

Abstract: A simple approach for preparing standard mixtures of volatile and semi-volatile organic compounds is reported. When placed in a closed container, standard mixture components partition between a polymeric material such as poly(dimethylsiloxane) (PDMS) and headspace to provide constant vapor concentrations. The granular form of heat-conditioned PDMS provides rapid equilibration with the headspace vapor and serves as a standard reservoir. Solid phase micro extraction (SPME) or gas-tight syringe can be used to del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…These analyte generators use polymeric sorbents such as PDMS or PS-co-DVB to sorb small organic molecules, which are then allowed to come to equilibrium with a sampling matrix in an enclosable vessel. 292,299 The most common embodiment of this device would be the standard HS generating vial configuration, where a standard HS is generated by placing the analyte-laden sorbent in a common HS vial with a septa cap. 300 As the sorbent has a much higher affinity for the analyte at equilibrium, the air contained in the vial remains at a relatively low concentration, and only a miniscule fraction of this standard is made available for extraction.…”
Section: ■ Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…These analyte generators use polymeric sorbents such as PDMS or PS-co-DVB to sorb small organic molecules, which are then allowed to come to equilibrium with a sampling matrix in an enclosable vessel. 292,299 The most common embodiment of this device would be the standard HS generating vial configuration, where a standard HS is generated by placing the analyte-laden sorbent in a common HS vial with a septa cap. 300 As the sorbent has a much higher affinity for the analyte at equilibrium, the air contained in the vial remains at a relatively low concentration, and only a miniscule fraction of this standard is made available for extraction.…”
Section: ■ Applicationsmentioning
confidence: 99%
“…220 Similarly, a vial based on a crushed PDMS sorbent with a 13 component mixture was used for the specific application of mass spectral tuning of field portable GC-MS instrumentation. 299 Likewise, a pentafluorobenzaldehyde (PFBAY) generating vial was used to facilitate the on-fiber derivatization of short-chain aliphatic amines from surface water samples. 301 In addition to the abovementioned specific applications, these standard generators are most commonly used as a simple quality control device to ensure stable response, as they can be easily placed in a heated block on a GC autosampler or transported on-site in a battery-operated block heater to perform quality control injections on portable GC-MS instrumentation before and after samplings.…”
Section: ■ Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was subsequently found that an appropriate standard gas generating vial could be produced by spiking a few milligrams of standard into a hydrocarbon based, ultra-low volatility mechanical pump-oil [11,14]. Furthermore Xie et al were also able to demonstrate that an easy-to-use multiple standard gas generating system could be prepared by spiking nanoliters of pure standard onto a solid PDMS powder [16]. These PDMS based vials were shown to exhibit acceptable intra-vial repeatability, as demonstrated by percent relative standard deviations (%RSD's) of about 4.5% after 114 headspace extractions were performed for 30 s using a 100 m PDMS fiber [16].…”
Section: Introductionmentioning
confidence: 95%
“…Furthermore Xie et al were also able to demonstrate that an easy-to-use multiple standard gas generating system could be prepared by spiking nanoliters of pure standard onto a solid PDMS powder [16]. These PDMS based vials were shown to exhibit acceptable intra-vial repeatability, as demonstrated by percent relative standard deviations (%RSD's) of about 4.5% after 114 headspace extractions were performed for 30 s using a 100 m PDMS fiber [16]. However, PDMS vials were still found to generate too high of a headspace concentration for trace applications, as several hundreds of nanograms of standards were still extracted.…”
Section: Introductionmentioning
confidence: 96%